OP68 Private health insurance status as a predictor of patient experience in public acute hospitals: evidence from a national healthcare survey in the republic of ireland. (3rd September 2019) - Huss, T; Foley, C; Boland, T; O'Carroll, T; O'Ceallaigh, D; Flynn, R
Abstract : Background: In Ireland, patients with private health insurance often receive treatment in publicly-funded hospitals. In the United Kingdom and Australia, a smaller but growing cohort of private patients are also receiving treatment in public hospitals. Surveys have shown that patients with private health insurance (PHI) expect higher standards of care, however, little research has been conducted to examine the association between PHI status and patient experience in public hospitals. This study draws on quantitative and qualitative evidence from the largest healthcare survey in Ireland to examine differences in experience between patients with PHI and those without. Methods: A cross-sectional survey design was used. 27, 100 participants in the National Patient Experience Survey who were admitted to a public acute hospital during May 2017 and 2018 responded to a 61-item questionnaire about their journey in hospital. Scales were constructed corresponding to the stages of care: admissions; care on the ward; examinations, diagnosis and treatment; discharge or transfer and overall experience. Multivariate regressions were used to explore differences in patient experience. Qualitative data related to PHI was gathered from three open-ended questions and analysed to explain differences in experience. Results: Controlling for sex, age, length of stay and route of admission, patients with PHI reported more negative experiences across four stages of care and overall experience compared to people without PHI (p<0.05). 210 free-text responses related to PHI. The qualitative analysis highlights that participants' expectations of their PHI benefits were not always fulfilled. Furthermore, a number of patients said that they felt pressured to sign private insurance forms when they were in fact entitled to free public care. Conclusion: In Ireland people with PHI are routinely treated in public hospitals. This study shows that having PHI is a negative predictor of patient experience in public hospitals. Patients expect preferential treatment due to their PHI status and may be disappointed if they do not receive it. The perceived gap between patients' expectations and actual experiences of care influences assessments of satisfaction with a service. Our findings contribute to a greater understanding of the expectations and implications of providing private care in public hospitals, both in Ireland and beyond. The learnings from our study should inform policymakers, service providers and frontline staff in managing patients' expectations in public hospitals.